Intestinal anti-inflammatory activity of esculetin and 4-methylesculetin in the trinitrobenzenesulphonic acid model of rat colitis - Witaicenis, Aline [UNESP]; Seito, Leonardo N. [UNESP]; Di Stasi, Luiz C. [UNESP] (Elsevier B.V., 2010)
Coumarins comprise a broad class of phenolic compounds that influences the formation and scavenging of reactive oxygen species and the processes involving free radical-mediated injury. In light of the antioxidant and anti-inflammatory properties of esculetin and 4-methylesculetin, the aim of this study was to investigate the effects of these compounds in an experimental model of rat colitis induced by trinitrobenzenesulphonic acid (TNBS). For this purpose, macroscopic (diarrhoea, extension of lesion, colonic weight/length ratio and damage score) and biochemical parameters (myeloperoxidase, alkaline phosphatase and glutathione) were evaluated. Our results reveal that these compounds, particularly 4-methylesculetin, may be effective for the treatment of intestinal inflammatory bowel disease. In the acute colitis model, esculetin promoted a reduction in the extension of the lesion accompanied by a reduction in the incidence of diarrhoea and restoration of the glutathione content. Similar effects were produced by the administration of 4-methylesculetin, which also inhibited the myeloperoxidase and alkaline phosphatase activities in the acute intestinal inflammatory process and in the model of colitis relapse. The effect of the esculetin and 4-methylesculetin on the inflammatory process may be related to their antioxidant and anti-inflammatory properties, as observed in this study. The evidence for better effects of 4-methylesculetin in comparison to those demonstrated by esculetin in both experimental settings could be attributed to the presence of the methyl group at C-4 of 4-methylesculetin. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Inflammatory bowel disease; Esculetin; 4-Methylesculetin; Coumarin; TNBS